The Business Case for Breastfeeding: Identifying Which Barriers and Facilitators Employers Prioritize When Supporting Breastfeeding Employees in the Workplace - Frieson, Tomeka; Muhammad, Tila; Belyea, Monica; Cole, Ayeisha; Ray, Natasha; Duffany, Kathleen (Journal of Human Lactation, 2026)
Keywords: Breast feeding; Breastfeeding; Phone; Private sector; Public health; Space (punctuation); breastfeeding; breastfeeding barriers; breastfeeding benefits; breastfeeding experience; breastfeeding knowledge; breastfeeding promotion; breastfeeding support; dept.hhs; maternal health; public health; qualitative methods; social support

Building Power for Health: CARE’s Community Health Leaders Program - Santilli, Alycia; Morales, Sofia I.; Hodgson, Nora; Williams, Janice M.; Alvarez-Diaz, Isabel; Cole, Ayeisha; Abrams, Jasmine; Breny, Jean M.; O’Connor Duffany, Kathleen (Health Promotion Practice, 2026)
Individuals who face the daily impact of health inequities and their social drivers have knowledge and invaluable insights about solutions that are feasible at the local level. Community organizing is a dynamic and proven approach for building power among residents to identify community priorities, advocate for change, and co-create solutions to community issues, which has been applied to advance community priorities in the public health field. To build on evidence and further cultivate a pathway to strengthen community power and capacity within a public health framework, the Community Alliance for Research and Engagement (CARE), a health equity-focused partnership among Southern Connecticut State University, Yale School of Public Health, and the New Haven community, developed and implemented a new initiative, the Community Health Leaders (CHL) Program. The CHL program provides a model for community-centered leadership development as a strategy for advancing health equity. By equipping residents with the skills and support needed to advocate for change, CHL contributes to strengthening community power. Ultimately, continued investment in programs like CHL has the potential to create responsive public health programs and policies, reduce health inequities, and improve health outcomes. © 2026 Society for Public Health Education
Keywords: advocacy; community health; community organizing; dept.hhs; empowerment; health disparities; health equity; health promotion; lay leader advisors; social determinants of health; training

Community-engaged design of a virtual diabetes prevention program intervention with care coordination - LaMonaca, Katherine; Campbell-Britton, Meredith; Duffany, Kathleen O’Connor; Comerford, Beth P.; Morales, Sofia I.; Ayettey, Rockiy G.; Astudillo, Katia; Swansiger, Mary; Kidd, Claudette; Rue, Bailee; Santilli, Alycia; Njike, Valentine Y.; et al. (BMC Health Services Research, 2026)
The Diabetes Prevention Program (DPP) is an evidence-based approach to prevent Type 2 Diabetes (T2D), the leading cause of morbidity and mortality in the United States. Despite demonstrated benefits, acceptability and uptake of DPPs remain low, especially among communities with low incomes at increased risk for diabetes. The Yale-Griffin Prevention Research Center led the design of a community-engaged virtual DPP (vDPP) intervention and assessed its feasibility of implementation in two contrasting settings.
Keywords: Prediabetes; Prevention; Telemedicine; Type 2 Diabetes; dept.hhs